The Strategy and Achievement in Reading Comprehension Of The Second Graders of SMA Muhammadiyah 1 Babat - Retno Ekowati (Magister Scientiae, 2013)
From the last-three-year document of national exam of English which emphasizes more reading comprehension, it can be known that some students scored high, some others scored low. The difference in achieving such a score may be influenced by the strategy use in reading. To know comprehensively reading strategy use and the reading comprehension achievement, this study aimed to find out: the reading strategies used by the high achieving students and the low achieving students, the most frequently used strategy by the students, and whether there is significant correlation between reading strategy and the reading comprehension achievement This non experimental study involves 56 second graders of the exact sciences program of SMA Muhammadiyah 1 Babat. Reading comprehension test and Survey of Reading Strategy (SORS) were used to collect the data. Data analyzing used tally and Pearson product moment. The findings are, the high achieving students used more reading strategies than low achieving students; the most frequently used strategy by among groups is problem solving, global, and support strategy; there is significant correlation between reading strategy and reading comprehension achievement by high achieving students and low achieving students. It means the better reading strategy used, the better reading achievement wil be and vice versa